Pain: A Culturally Informed Experience - David Ng (Pain Research and Management)
I was raised in North America - a culture and society in which the education emphasizes knowledge about science, its methods and its principles. The scientific method of understanding, coupled with the rudimentary knowledge that I was taught in high school biology, resulted in my conceptualization of pain as an objective truth. Pain, as I believed for a long time, was a bodily sensation with an expression that was more or less universal; to me, pain was simply the sensation that the brain experiences as a response to noxious stimuli. The pain sensation protects us from things that can hurt us; it is a warning sign that something in us is physically amiss. Thus, everybody physically reacts to the touch of a flame or experiences abdominal pain when there is appendicitis. Even now, in medical school, the pain education that I have received so far has only involved the physiology or mechanics of pain. Pain, as a physiological condition, operates independent of cultural context. However, in considering the experience of pain that my grandmother has endured, I realize that pain is much more than a mechanical bodily sensation effected by the nervous system in response to stimulus. Pain is a human experience, and as such, it is highly individualized and subjective. The proper diagnosis, care and treatment of pain necessitate a holistic understanding of pain, its physiology and its context (1).